Agenda
039-0077-001 BASQUE CHILDREN'S COMMITTEE. AGENDA Meeting of July 20th, 1937. 1. Minutes of the Meeting of July 5th, 1937. 2. Business arising out of the Minutes. 3. Apologies for Absence. 4. Correspondence: Hull. 5. Co-options to the Committee. 5a. Accounts (i) Circulated statement; (ii) Authorization for Sec. to sign cheques. (iii) Children's money-raising perfs. 6. Problem of the Older Boys (a) Scarborough (b) Carmarthen. 7. Report from Camp. 8. New Centres. 9. Reports from Centres: (a) Salvation Army (b) Roman Catholic Homes. (c) Problem of the Senoritas (i) Salvation Army (ii) Derby (iii) Bristol 10. Health of the Children: (a) Tubercular meningitis case in Bristol Infirmary. (b) Mental Cases (two) (c) Accident at the Camp. 11. "Individual" Holidays for Children. 12. Date of next meeting. 13. Any other business. 292/946/39/77